Desenvolvimento e aprendizagem de alunos com autismo em sala de aula - Redmerski, Monalisa de Oliveira Miranda (2018)
Since education is an important basis for individual and collective development, teaching becomes essential for all. Based on this assertion, the present work aims at analysing aspects of the educational process that contribute to the integral development of students with autism in elementary education. The theoretical discussion was based on legal norms and on authors such as Vygotsky (1991; 2000, 2003), Cunha (2011; 2013a), Mantoan (2015). The work adopts a qualitative approach, of an exploratory nature, based on multiple case studies, compatible with the richness and uniqueness of the investigated object. The collection and generation of data were performed through the following techniques: observations, interviews and documentary analysis. Data analysis was guided by the assumptions of content analysis, as proposed by Bardin (2012). Results showed that resources used by teachers to accompany the development of autistic students in the classroom were activities, observations, adapted assessments, oral expression and behaviour analysis. The choice of these resources by teachers is based on the characteristics and interests of their respective autistic students. In addition, it was also verified that the socio-affective aspects of teachers were perceived by these students as an important element in their decision to go to school.